Effect of Steel Truss Configuration on Bridge Structural Strength and Seismic Response - Lalu Samsul Aswadi; Dwi Sat Agus Yuwana; Bina Arumbinang Wajdi; Aisya Bhanuwati; Reyhan Daffa (Jurnal Teknik Sipil dan Perencanaan, 2026)
Located within the Pacific Ring of Fire, Indonesia experiences high seismic intensity, posing a risk of structural damage to bridges; thus, seismic load considerations are imperative in bridge engineering. Although bridge seismic analysis has been conducted, comparative studies of truss configurations under seismic loads remain limited. This study analyzes the influence of truss configurations, including Howe, Pratt, Warren, Quadrangular Warren, Whipple, Camel Back, Baltimore, K-Truss, and Petit Truss, under seismic loads through deflection and Demand Capacity Ratio (DCR) parameters. The analysis was performed using Midas Civil, a Finite Element Method software, while seismic loading was applied using the response spectrum method. The results show that the Camel Back Truss achieves the highest structural efficiency, yielding the lowest DCR, with a maximum of 0.064693 and 0.1503 for the mean. Regarding serviceability, Petit Truss exhibited the minimum deflection values of 0.02735 m, 0.02482 m, and 0.02493 m for Service I (TD), Service I (TT), and Extreme I, respectively. Overall, Camel Back Truss provides the best structural performance by maintaining the lowest stress ratio and the second-lowest deflection, recorded at 0.02725 m and 0.03897 m under Service I and 0.02818 m under Extreme I loads, respectively.